2002
DOI: 10.1093/jat/26.7.411
|View full text |Cite
|
Sign up to set email alerts
|

Improved Screen and Confirmation Test of 7-Aminoflunitrazepam in Urine Specimens for Monitoring Flunitrazepam (Rohypnol) Exposure

Abstract: Confirmed and alleged misuses of flunitrazepam (FM2, Rohypnol) have brought about serious interest in the development of an analytical methodology that can be effectively used for preliminary screen and confirmatory test of FM2 (or its metabolites) in urine specimens under high-volume settings. Reported methods do not serve this need well for the following reasons: (1) common benzodiazepine (BZ) immunoassays (IAs) have broad cross-reactivities toward widely prescribed BZs (and their metabolites) and are theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Flunitrazepam can be analysed via traditional analytical methodologies such as Immunoassay, Liquid Chromatography-Mass Spectroscopy (LC-MS) [6][7][8][9][10] or Gas Chromatography-Mass Spectroscopy (GC-MS) [11][12][13] which have successfully been applied for their quantification in biological matrixes. Of note is the analysis of oral fluid (saliva) by Wang et al [12] who found that typical benzodiazepine immunoassays have a broad cross reactivity towards widely prescribed benzodiazepines and found that due to the low dosage of the drug these systems lead to an unacceptable number of false negatives. More recently, Moore et al [7] described a methodology where benzodiazepines in oral fluid samples were analyzed using the Quantisal collection device and quantified via Solid Phase Extraction and LC-MS.…”
Section: Introductionmentioning
confidence: 99%
“…Flunitrazepam can be analysed via traditional analytical methodologies such as Immunoassay, Liquid Chromatography-Mass Spectroscopy (LC-MS) [6][7][8][9][10] or Gas Chromatography-Mass Spectroscopy (GC-MS) [11][12][13] which have successfully been applied for their quantification in biological matrixes. Of note is the analysis of oral fluid (saliva) by Wang et al [12] who found that typical benzodiazepine immunoassays have a broad cross reactivity towards widely prescribed benzodiazepines and found that due to the low dosage of the drug these systems lead to an unacceptable number of false negatives. More recently, Moore et al [7] described a methodology where benzodiazepines in oral fluid samples were analyzed using the Quantisal collection device and quantified via Solid Phase Extraction and LC-MS.…”
Section: Introductionmentioning
confidence: 99%
“…Cozart ELISA was proved to be more effective than Beckman and CEDIA reagents in an improved screen and confirmation test of urine samples for preliminary detection of flunitrazepam exposure. It is because Beckman is least sensitive to detect the presence of 7-aminoflunitrazepam, and CEDIA is though sensitive most its cross-reacting characteristics toward other benzodiazepines substantially reduces its effectiveness for monitoring flunitrazepam [116]. Utilizing a bioconjugate of gold nanoparticles and enzyme-labeled antibody as a signal probe increases the sensitivity of a traditional ELISA for 7-ANZP by nearly 20 times [117].…”
Section: Immunoassaysmentioning
confidence: 99%
“…The four immunoassay urine screening kits; Roche Benzodiazepine PlusKIMS assay, Microgenics CEDIA Benzodiazepine assay, Microgenics CEDIA high sensitivity assay with β-glucuronidase, and Microgenics DRI reagent ready Benzodiazepine assay, were evaluated to investigate their performance in forensic urine analysis [122][123][124]. In all cases confirmatory tests have been done either by HPLC-MS [108,120,122,123] or GC-MS method [10,112,[114][115][116].…”
Section: Immunoassaysmentioning
confidence: 99%